Multicultural Counseling Model in Cultivating Religious Moderation in Adolescents - Viola Delita; Kusnadi; Bela Janare Putra (al-Afkar, Journal For Islamic Studies, 2025)
This study is entitled "Multicultural Counseling Model in Cultivating Religious Moderation Attitudes in Adolescents". This study is motivated by religious moderation which is an ongoing challenge, the lack of religious moderation attitudes is caused by the lack of awareness of national commitment, tolerance, anti-violence and accommodating to local culture. So that efforts need to be made in order to foster religious moderation attitudes, namely by using a multicultural counseling model. The purpose of this study, first, is to determine the description of religious moderation attitudes in adolescents in Gunung Gare Village before multicultural counseling is carried out. Second, to determine the description of religious moderation attitudes in adolescents in Gunung Gare Village after multicultural counseling is carried out. Third, to determine the effectiveness of the multicultural counseling model in fostering religious moderation attitudes in adolescents in Gunung Gare Village. This research method uses a quantitative approach with an experimental research type and a one group pretest-posttest design. The sample in this study was 6. The data collection technique in this study used documentation and questionnaires with a total of 32 statements that had been tested for validity r count > r table with a range of r count values 0.364-0.747 and r table 0.361. The data analysis technique used normality test and hypothesis test. The results of the study showed an attitude of religious moderation in adolescents with an average pretest value of 76 then increased as seen from the average posttest value of 107. From the results of the normality test, a pretest of 0.301 and a posttest of 0.616 were obtained and the T test showed that the significant value (2-tailed) of 0.001 was less than 0.05, meaning that Ha was accepted and H0 was rejected, and there was a difference between the pretest and posttest. Therefore, the multicultural counseling model is effective in fostering an attitude of religious moderation in adolescents in Gunung Gare Village.